Determinants of Bank Risk-Taking: The Role of Capital Adequacy Ratio, Return on Equity to Total Assets, and Loan to Deposit Ratio in The Indonesian Banking Sector - Angkut, Angkut; Yamaly, Fadhil; Candera, Mister (Baileo: Jurnal Sosial Humaniora, 2025)
This study aims to analyze the factors that determine the level of banking risk-taking in Indonesia, focusing on the role of the Capital Adequacy Ratio (CAR), Return on Equity to Total Assets (RETTA), and Loan to Deposit Ratio (LDR). The study employs a multiple linear regression method to examine the influence of independent variables on Bank Risk Taking, measured using Non-Performing Loans (NPL). The data used in this research come from the banking sector in Indonesia, applying a quantitative approach. The findings indicate that CAR has a positive and significant impact on Bank Risk Taking, with a regression coefficient of 3.021. This suggests that an increase in CAR tends to raise NPL, implying that banks with stronger capital tend to take higher risks. Furthermore, RETTA also has a positive and significant effect on Bank Risk Taking, with a regression coefficient of 0.531, meaning that an increase in RETTA contributes to higher NPL. Conversely, LDR has a negative and significant impact on Bank Risk Taking, with a regression coefficient of -0.020, indicating that an increase in LDR can reduce NPL. The novelty of this study lies in the simultaneous analysis of three key indicators influencing bank risk-taking, providing a comprehensive perspective on the relationship between capital structure, profitability, and liquidity in Indonesia’s banking sector. These findings have implications for the development of social sciences and humanities, particularly in economics and financial management, by highlighting the importance of banking risk management policies. Recommendations include strengthening regulations and supervision over CAR and RETTA to control higher risk exposure, as well as optimizing LDR to maintain financial stability in Indonesia’s banking sector.